2021
DOI: 10.1021/acs.joc.1c00443
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-Catalyzed Intramolecular Double Hydrofunctionalization of Alkynes. Synthesis of Spirocyclic Hemiaminal Ethers and Their Lewis Acid-Mediated Cleavage/Nucleophilic Addition

Abstract: Metrics & MoreArticle Recommendations * sı Supporting InformationABSTRACT: [RuCl 2 (p-cymene)] 2 /AgNO 3 -catalyzed intramolecular double hydrofunctionalization of internal alkynes having nitrogen and oxygen nucleophilic groups at appropriate positions provided a series of spirocyclic hemiaminal ether derivatives in good to excellent yields. The product spiro-hemiaminal ethers underwent Lewis acid-mediated chemoselective cleavage, and in situ-generated iminium/oxocarbenium ions could be trapped with nucleophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…The formation of both regioisomers can be explained either by a 6- endo-dig or 5- exo-dig cyclization from any of the hydroxyl groups, and the regioselectivity was influenced by steric and electronic effects, reaction conditions, and the metal catalyst. As an example, the same reaction using Ir( i ) 20 or Au( i ) 16 c catalysis provided 4a as the major regioisomer while Ru( ii ) 13 or Au( iii ) 17 led to 5a as the major spiroketal. In our case, we observed that the regioselectivity changed slightly when DCE was used as the solvent (1 : 2.7), but remained unaltered on using higher concentrations in toluene or increasing the catalyst loading (5 mol%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of both regioisomers can be explained either by a 6- endo-dig or 5- exo-dig cyclization from any of the hydroxyl groups, and the regioselectivity was influenced by steric and electronic effects, reaction conditions, and the metal catalyst. As an example, the same reaction using Ir( i ) 20 or Au( i ) 16 c catalysis provided 4a as the major regioisomer while Ru( ii ) 13 or Au( iii ) 17 led to 5a as the major spiroketal. In our case, we observed that the regioselectivity changed slightly when DCE was used as the solvent (1 : 2.7), but remained unaltered on using higher concentrations in toluene or increasing the catalyst loading (5 mol%).…”
Section: Resultsmentioning
confidence: 99%
“…10 However, the regioselectivity is somehow variable depending on the substrate, catalyst and reaction conditions, with this issue being a topic of current interest. 11 Hitherto, the synthesis of benzannulated spiroketals from alkyne diols has been disclosed under transition metal catalysis using Hg( ii ), 12 Ru( ii ), 13 Rh( i ) and Ir( i ), 14 Ag( i ) 15 and Au( i ) 16 or Au( iii ) 17 but the use of main group metals, such as indium, remains unknown (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…5-Chlorine was found to be the most favorable with a 95% yield of the product (15), better than both 3-and 6-chlorine pyridine hydrazine (14 and 16, respectively). However, when we introduced multiple electronwithdrawing groups to the pyridine ring, the yield decreased to 40% (17). When the R group was changed to p-methylphenyl hydrazine, the desired product could be obtained in a 45% yield (18).…”
mentioning
confidence: 99%
“…16 Subsequently, the nucleophilic nitrogen atom of the hydrazine moiety attacks the sulfur atom of isothiazole, leading to the cleavage of the N−S bond under the action of Ti(O i Pr) 4 and producing the intermediate III. 16,17 After the elimination of HCl, the desired products 1,2,3-thiadiazoles are produced and Ti(O i Pr) 4 is regenerated (see Figure S2).…”
mentioning
confidence: 99%
See 1 more Smart Citation